Chitin synthase in Candida albicans: comparison of digitonin-permeabilized cells and spheroplast membranes. - Georgopapadakou, N H (1985)
The treatment of Candida albicans (yeast form) with digitonin or dimethyl sulfoxide permeabilized cells and caused the activation of chitin synthase in situ. Endogenous activation was completely prevented by the sulfhydryl reagents N-ethylmaleimide, p-chloromercuribenzoate, and 5,5'-dithiobis(2-nitrobenzoic acid); partially prevented by the protease inhibitors antipain, leupeptin, and N alpha-tosyl-L-lysyl chloromethyl ketone; and also partially prevented by EDTA. Thus, a clostripain-like protease may be involved in the endogenous activation phenomenon. The pH activity profile, cofactor requirements, and kinetic parameters of the endogenously activated chitin synthase were identical to those of the trypsin-activated enzyme in protoplast membranes.